Modified in situ Hybridization Chain Reaction Using Short Hairpin DNAs - Tsuneoka, Yousuke; Funato, Hiromasa (Frontiers in Molecular Neuroscience, 2020)
The visualization of multiple gene expressions in well-preserved tissues is crucial for the elucidation of physiological and pathological processes. In situ hybridization chain reaction (HCR) is a method to visualize specific mRNAs in diverse organisms by applying a HCR that is an isothermal enzyme-free nucleotide polymerization method using hairpin DNAs. Although in situ HCR is a versatile method, this method is not widely used by researchers because of their higher cost than conventional in situ hybridization (ISH). Here, we redesigned hairpin DNAs so that their lengths were half the length of commonly used hairpin DNAs. We also optimized the conjugated fluorophores and linkers. Modified in situ HCR showed sufficient fluorescent signals to detect various mRNAs such as Penk, Oxtr, Vglut2, Drd1, Drd2, and Moxd1 in mouse neural tissues with a high signal-to-noise ratio. The sensitivity of modified in situ HCR in detecting the Oxtr mRNA was better than that of fluorescent ISH using tyramide signal amplification. Notably, the modified in situ HCR does not require proteinase K treatment so that it enables the preservation of morphological structures and antigenicity. The modified in situ HCR simultaneously detected the distributions of c-Fos immunoreactivity and Vglut2 mRNA, and detected multiple mRNAs with a high signal-noise ratio at subcellular resolution in mouse brains. These results suggest that the modified in situ HCR using short hairpin DNAs is cost-effective and useful for the visualization of multiple mRNAs and proteins.